Exploring the Relationship Between Public Stigma, Self-Stigma, and Counselling Help-Seeking Intentions Among Adolescents in Madrasah - Ariyati, Ika (COUNS-EDU: The International Journal of Counseling and Education, 2023)
To improve the mental well-being of adolescents is that there is no intention to seek psychological help. This study aims to explore the relationship between public stigma, self-stigma, and the intention to seek psychological help among adolescents who are educated in Madrasas. The method used in this study is quantitative with a cross-section design. This study involved 580 participants, who were invited using convenience and snowball sampling methods. The instruments used were cultural orientation, self-public, social-network stigma, attitudes towards seeking help, intention to seek counseling, and demographic questions. The main findings suggest that adolescents who experience high levels of public stigma tend to have higher levels of self-stigma, which further influences their intention to seek help (psychologically). In addition, cultural orientation also shapes perceptions and attitudes toward seeking counseling help. The findings of this study highlight the urgent need for targeted interventions to reduce public stigma against mental health problems, which can be provided by educational institutions, mental health organizations, as well as governments to create an environment that supports the mental well-being of adolescents.